Medicine 150 EMQs for finals - Capewell, David (Get ahead!, 2010)
Get ahead! is a brand new essential revision series for medical and surgical finals. Each title contains practice questions similar to those you can expect in the real exam. The series stands out in its use of subject summaries that include all the detail you would need from a larger textbook - but we've waived the waffle! If you are looking for a comprehensive, reliable, effective revision aid, then look no further than Get ahead!